Mining the phytomicrobiome to understand how bacterial coinoculations enhance plant growth - Maymon, Maskit; Martínez-Hidalgo, Pilar; Tran, Stephen S.; Ice, Tyler; Craemer, Karena; Anbarchian, Teni; Sung, Tiffany; Hwang, Lin H.; Chou, Minxia; Fujishige, Nancy A.; Villella, William; Ventosa, Jerome; et al. (Frontiers in Plant Science, 2015)
In previous work, we showed that coinoculating Rhizobium leguminosarum bv. viciae 128C53 and Bacillus simplex 30N-5 onto Pisum sativum L. roots resulted in better nodulation and increased plant growth. We now expand this research to include another alpha-rhizobial species as well as a beta-rhizobium, Burkholderia tuberum STM678. We first determined whether the rhizobia were compatible with B. simplex 30N-5 by cross-streaking experiments, and then Medicago truncatula and Melilotus alba were coinoculated with B. simplex 30N-5 and Sinorhizobium (Ensifer) meliloti to determine the effects on plant growth. Similarly, B. simplex 30N-5 and Bu. tuberum STM678 were coinoculated onto Macroptilium atropurpureum. The exact mechanisms whereby coinoculation results in increased plant growth are incompletely understood, but the synthesis of phytohormones and siderophores, the improved solubilization of inorganic nutrients, and the production of antimicrobial compounds are likely possibilities. Because B. simplex 30N-5 is not widely recognized as a Plant Growth Promoting Bacterial (PGPB) species, after sequencing its genome, we searched for genes proposed to promote plant growth, and then compared these sequences with those from several well studied PGPB species. In addition to genes involved in phytohormone synthesis, we detected genes important for the production of volatiles, polyamines, and antimicrobial peptides as well as genes for such plant growth-promoting traits as phosphate solubilization and siderophore production. Experimental evidence is presented to show that some of these traits, such as polyamine synthesis, are functional in B. simplex 30N-5, whereas others, e.g., auxin production, are not.